Implementasi Pembelajaran blended learning di MI - MASKUR Maskur Maskur; Muhammad Khoirul Anwar; Trianah Trianah Trianah (Universitas Wahid Hasyim Semarang, 2021)
AbstractThe Covid-19 pandemic is the reason for these two semesters of online learning. Because the progression of cases is slowing, schools have more leeway to hold Limited Face-to-Face Meetings. Learning in a mixed learning environment with only a few face-to-face meetings is possible. The purpose of this study was to determine how blended learning was implemented at the research site. The lack of face-to-face implementation has significant ramifications that various institutions must address, particularly the readiness to provide the infrastructure required for both offline and online learning in the classroom. MI NU 28 Roudlotussibyan Kendal implements learning in two ways: offline and online, or more precisely, blended learning. To collect data, this study employs qualitative research methods such as observation, documentation, and interviews. According to the study's findings, blended learning is implemented with a limited amount of face-to-face interaction and the use of numerous learning platforms as the media, such as Google Classroom, Google Meet, and WhatsApp. Blended learning implementation is hampered by a lack of appropriate infrastructure, internet network limits, and instructor challenges in classroom management. When compared to using only online learning, the benefits of implementing blended learning include increased student engagement, improved learning outcomes, and increased student motivation to learn.Key Words: Blended learning, Madrasah ibtidaiyah, Madrasah ibtidaiyah